Sociocultural Integration of Adults with Autism in the "12MM!" Project. - A.S. Steinberg; A.L. Voskov; E.M. Klevtsova (Moscow State University of Psychology and Education, 2022)
The problem of socialization of people with autism spectrum disorders (ASD) is paid more and more attention. The suggested "12MM!" project resolves a lot of issues with social integration and cultural development of young people and adults with ASD. The aim of "12MM!" project is organizing group visits to museums and other cultural institutions (theaters, exhibitions, excursions etc.) by adults with ASD and participation in inclusive environment implementation in cultural institutions. Its key feature is participation of adults with ASD in events for organizing an accessible environment in cultural institutions. With participation of autistic experts of the project sensory audit of 12 museum was conducted and more than 30 lectures, seminars and other events for museum staff was organized. They also took participation in the development of guidelines. Such approach is innovative and agrees with the social model of disability and "nothing about us with us" principle. The results of almost three years of the project work are reflected in the project participants' query. It showed that they are interested by events themselves and by the possibility of communication with other people including ones with ASD. They are also attracted by friendly guides and accessibility of excursions language. Majority of participants estimated inclusivity of museums environments as acceptable. Among possible means of improving accessibility participants pointed at training of guides and other museum staff, making navigational histories (detailed description of routes to museums) and sensory safety maps.